1999
DOI: 10.1016/s0001-706x(99)00029-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological studies of blood, tissue fluid, lymph and lymph nodes in patients with acute dermatolymphangioadenitis (DLA) in course of ‘filarial’ lymphedema

Abstract: Filarial lymphedema is complicated by frequent episodes of dermatolymphangioadenitis (DLA). Severe systemic symptoms during attacks of DLA resemble those of septicemia. The question we asked was whether bacterial isolates can be found in the peripheral blood of patients during the episodes of DLA. Out of 100 patients referred to us with 'filarial' lymphedema 14 displayed acute and five subacute symptoms of DLA. All were on admission blood microfilariae negative but had a positive test in the past. Blood bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 18 publications
(15 reference statements)
1
28
0
Order By: Relevance
“…Surprisingly, in the ICLNs, Escherichia-and Pseudomonas-associated OTUs were the most abundant OTUs, with Ͼ30% of all reads generated in this study. Escherichia and Pseudomonas are known to be pyogenic organisms, as is Acinetobacter junii, having already been isolated from purulent tissues and lymph fluid (52,53). This is the first time Escherichia, Pseudomonas, and Acinetobacter species have been associated with purulence in porcine ICLNs.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, in the ICLNs, Escherichia-and Pseudomonas-associated OTUs were the most abundant OTUs, with Ͼ30% of all reads generated in this study. Escherichia and Pseudomonas are known to be pyogenic organisms, as is Acinetobacter junii, having already been isolated from purulent tissues and lymph fluid (52,53). This is the first time Escherichia, Pseudomonas, and Acinetobacter species have been associated with purulence in porcine ICLNs.…”
Section: Discussionmentioning
confidence: 96%
“…Clearly, additional efforts are needed to define the specific organisms that may be associated with recurrent infections and ADL. 16 The relationship, if any, between filarial exposure and acute attacks remains unresolved. Kar and others suggested that antifilarial antibody levels decreased following an acute attack, but we did not see a relationship between antifilarial antibody levels and either the frequency or the time interval since the last attack.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, lymphatic damage associated with the presence of adult worms leads to impaired lymph flow and establishes conditions favorable for the development of secondary bacterial infections, causing further vessel damage and worsening of lymphedema. [16][17][18] The hypothesis that bacterial infections contribute to progression of ''filarial'' disease is supported by studies that show that bacteria can be isolated from the blood and lymph of persons experiencing acute attacks and that acute ADL attacks are prevented by improving skin hygiene and by treating entry lesions with topical antibiotics and antifungal creams. 12,16,19 These observations suggest that bacterial infections are a determinant of disease progression; however, they do not rule out a potential role for immune responses to filarial, bacterial or fungal antigens in triggering the inflammation associated with ADL or in the initiation or progression of processes leading to lymphedema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] The influence of bacterial cells, with colonization of traumatized tissues, either directly from the damaged skin or reaching the site of trauma by lymphatics from the foot, should also be considered. 9 The macrophages that scavenge cellular debris, the subcellular fragments from damaged cells, the fragments of ground matrix, and vasoregulatory factors, are transported from the site of injury to the LNs and may evoke the cellular and humoral reaction.…”
mentioning
confidence: 99%